Application of Modified OPTICS Algorithm in E-Commerce Sites Classification and Evaluation - Yu, Zhuoxi; Jin, YuJia; Parmar, Milan; Wang, Limin (Journal of electronic commerce in organizations, 2016)
In the era of the development in network economy, e-commerce sites' operational efficiency is in relation to the development of enterprises. Thus, how to evaluate e-commerce sites have become a hot topic. Due to the evaluation index of e-commerce sites have the characteristics of high dimension and data inhomogeneity, the new method combines PCA with the improved OPTICS algorithm to classify and evaluate the e-commerce demonstration enterprise websites. Firstly, using PCA to reduce the dimension of high-dimensional data. Secondly, for the limitation of OPTICS algorithm in dealing with sparse points, then using the improved OPTICS algorithm in clustering low-dimensional data to evaluate the effect of e-commerce sites and make suggestions.